HYDRAULIC DESIGN OF SMALL EARTH CASCADE DAM FOR DRYLAND GOGO RICE PLANTATION - Prakoso, Wahyu Gendam; Irawan, Pengki (University Muhammadiyah Jakarta, 2024)
The irrigation of gogo rice plantataion on dryland is not extensively developed in Indonesia. Design for the earthfill dam using a combination of hydrological analysis and open-channel hydraulic modeling. Hydrological modeling is conducted by transforming rainfall into runoff using the rainfall- run off model. The hydraulic design involves determining the capacity of the earthfill dam. Hydraulic models and simulations help estimate the potential inflow rates and assess the dam's ability to handle peak flows during extreme weather events. Spillway dimensions are determined based on the dam's design flood criteria, hydraulic modeling, and safety standards. The design of small-scale earthfill dams in cascade to meet the irrigation water needs for dryland paddy plantations in West Tulang Bawang, Lampung, consists of 2 dams (Dam 1: upstream; Dam 2: downstream). Dam 1 effective reservoir 74039 m3, and the inundation area reaches 10846 m2. The inflow discharge is 7.3 m3/second. Total storage volume dam 2 reaching 77023 m3, and the inundation area is 22000 m2. The inflow discharge is 14.18 m3/second. To ensure dam safety, a spillway is designed with an ogee crest using a square-section control with effective widths of 3.0 m for Dam 1 and 4.5 m for Dam 2. Flood reduction in the downstream part of Dam 2 reaches 22% with 10.99 14.18 m3/second outflow discharge and is estimated to be safe to prevent failure due to overtopping hazards. Further research is needed for extreme emergency action plans with simultaneous dam failure scenarios.